Internal Validation Guide of the Amp F_STR Identifiler PCR by Using Quantifiler™ Y Human Male DNA Quantification for Use Forensic Laboratories - AL-Zubaidi, Mohammed Mahdi (Al-Nahrain Journal of Science, 2018)
Fifty samples of buccal swabs were collected from male oral cavity, then genomic DNA was extracted from each sample by two methods, the manual organic phenol chloroform methods and prepfiler forensic extraction kit methods.The concentration of genomic DNA extracted was measured by using Quantifiler® Duo Kit throughout detection the SRY (FAM™-labeled probe), RPPH1(VIC®-labeled probe) and an Internal Positive Control-IPC (NED™-labeled probe).Results showed that the concentration of genomic DNA in buccal swab was ranged between 0.26 and 9.422 ng/ul. these samples work with a serial dilution decimal, as well as PCR .Then introduced to the device 3130xl Genetic Analyzer 16-capillary array system, The results showed that the concentrations is preferable which is located between 25-50 pg, as this did not appear in the concentrations of any problems and the emergence of the peaks clearly Compared with the ALLELIC ladder and positive control, After the election concentrations were chosen Thresholds, Peak amplitude thresholds.